Positive plate, battery monomer, battery and electric device

By controlling the coordination of conductive agent and powder resistivity, the positive electrode active material is arranged layer by layer, which solves the electrical performance problems caused by the difference in conductivity in the positive electrode sheet, improves the capacity retention rate and energy density, and reduces the production under high temperature and high voltage conditions Gas risk.

CN119208520AActive Publication Date: 2024-12-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310752272.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-27
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

In the positive electrode sheet using multiple positive electrode active materials, there is still a problem of poor electrical performance after layering, mainly due to the difference in conductivity between the layers of each positive electrode active material, which leads to uneven current, which affects the capacity retention rate and energy density. .

Method used

By controlling the addition amount of the first conductive agent combined with the first positive electrode active material with a poor electronic conductivity and the powder resistivity of the second positive electrode active material with a good electronic conductivity, the conductivity between the layers of the positive electrode active material is reduced. The possibility of current inhomogeneity is reduced by layering settings, polyanionic positive electrode materials and ternary system materials are used to improve safety performance and energy density.

Benefits of technology

The electrical performance of the positive electrode sheet is improved, the capacity retention rate is improved, the addition of conductive agent is reduced, the gas production deterioration under high temperature and high voltage conditions is reduced, and the circulation performance and energy density are taken into account.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208520A_ABST
    Figure CN119208520A_ABST
Patent Text Reader

Abstract

The invention discloses a positive plate, a battery monomer, a battery and an electric device and belongs to the technical field of batteries. The positive plate comprises positive electrode active material layers, the positive electrode active material layers comprise a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer comprises a first positive electrode active material and a first conductive agent, and the second positive electrode active material layer comprises a second positive electrode active material; the electronic conductivity of the second positive electrode active material is greater than that of the first positive electrode active material; the powder resistivity F of the second positive electrode active material under 8Mpa by taking omega.cm as a unit and the weight ratio C of the first conductive agent in the first positive electrode active material layer meet the following relation: # imgabs0 # can reduce the conductivity difference between the first positive electrode active material layer and the second positive electrode active material layer, so that the electrical performance exertion of the whole positive plate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet, a battery cell, a battery and an electrical device. Background Art

[0002] In a positive electrode sheet using multiple positive electrode active materials, in order to reduce the possibility of current unevenness between the positive electrode active materials, the positive electrode active materials are usually arranged in layers. However, the positive electrode sheet after the layered arrangement still has the problem of poor electrical performance. Summary of the invention

[0003] In view of the above problems, the present application provides a positive electrode sheet, a battery cell, a battery and an electrical device, which can reduce the conductivity difference between each positive electrode active material layer and improve the electrical performance.

[0004] In a first aspect, the present application provides a positive electrode sheet, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer includes a first positive electrode active material and a first conductive agent, the second positive electrode active material layer includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, and the powder resistivity F of the second positive electrode active material at 8 MPa in units of Ω·cm and the weight proportion C of the first conductive agent in the first positive electrode active material layer satisfy the following relationship:

[0005] In the technical solution of the embodiment of the present application, by controlling the addition amount C of the first conductive agent matched with the first positive electrode active material with poor electronic conductivity and the powder resistivity F of the second positive electrode active material with good electronic conductivity at 8Mpa to meet To reduce the difference in conductivity between the first positive electrode active material layer and the second positive electrode active material layer, thereby improving the electrical performance of the entire positive electrode sheet. At the same time, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby making the positive electrode sheet have a higher capacity retention rate in the early stage of the cycle.

[0006] In some embodiments, the powder resistivity F of the second positive electrode active material in Ω·cm at 8 MPa and the weight proportion C of the first conductive agent in the first positive electrode active material layer satisfy the following relationship:

[0007] In the above implementation process, by controlling the addition amount C of the first conductive agent matched with the first positive electrode active material with poor electronic conductivity and the powder resistivity F of the second positive electrode active material with good electronic conductivity at 8Mpa to meet The difference in conductivity between the first positive electrode active material layer and the second positive electrode active material layer can be further reduced, and the electrical performance of the entire positive electrode sheet can be further improved. At the same time, the addition of the first conductive agent can be further reduced, and the deterioration of the gas generation by the first conductive agent under high temperature and high voltage conditions can be reduced.

[0008] In some embodiments, the powder resistivity of the second positive electrode active material at 8 MPa is 10 to 80 Ω·cm; and / or

[0009] The weight percentage of the first conductive agent in the first positive electrode active material layer is 1.9% to 2.8%; and / or

[0010] The powder resistivity of the first conductive agent at 8 Mpa is ≤0.025 Ω·cm.

[0011] In the above implementation process, by controlling the powder resistivity of the second positive electrode active material, the content of the first conductive agent in the active layer of the first positive electrode material is kept within a relatively suitable range, the proportion of the first positive electrode active material is maintained within a relatively high range, and the decrease in the energy density of the entire positive electrode sheet is reduced. At the same time, the powder resistivity of the second positive electrode active material at 8Mpa is within the range of 10 to 80Ω·cm, which can also take into account its own cycle performance.

[0012] In some embodiments, the first cathode active material comprises a ternary system material; and / or

[0013] The second positive electrode active material includes a polyanion positive electrode material.

[0014] In the above implementation process, polyanion positive electrode materials usually exhibit good safety performance, and ternary system materials usually exhibit higher energy density. Using polyanion positive electrode materials as the second positive electrode active material and ternary system materials as the first positive electrode active material can make the positive electrode sheet have both higher safety performance and higher energy density.

[0015] In some embodiments, the polyanion cathode material comprises LiMPO 4 , M includes Mn and non-Mn elements, the non-Mn elements include one or both of a first doping element and a second doping element, the first doping element is manganese-doped, and the second doping element is phosphorus-doped.

[0016] Optionally, the first doping element includes one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge.

[0017] Optionally, the second doping element includes one or more elements of B, S, Si and N.

[0018] Optionally, the polyanion cathode material includes Li 1+x Mn 1-y A y P 1-z R z O 4 , wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.

[0019] Optionally, the polyanion cathode material includes Li h A i Mn 1-j B j P 1-k C k O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.

[0020] In some embodiments, the polyanionic cathode material further has a coating layer comprising carbon.

[0021] In the above implementation process, the conductivity of the positive electrode active material is improved by introducing a carbon-containing coating layer. At this time, the structure of the positive electrode active material is actually LiMPO 4 The core has a core-shell structure in which the surface of the core is covered with a coating layer.

[0022] In some embodiments, the second positive electrode active material has a powder resistivity of 20 to 50 Ω·cm at 8 MPa.

[0023] In the above implementation process, the polyanion positive electrode material such as LiMPO 4The powder resistivity of the [material] often shows a negative correlation with the surface carbon coating amount. The lower the powder resistivity, the higher the carbon coating amount. However, this surface carbon coating layer will also deteriorate the gas generation during storage under high-temperature and high-voltage conditions. Therefore, by controlling the powder resistivity of the second positive electrode active material to be 20 - 50 Ω·cm at 8 Mpa, the possibility of significantly deteriorating the gas generation can be reduced, and at the same time, its own cycle performance can be taken into account.

[0024] In some embodiments, the ternary system material includes nickel-cobalt-manganese ternary material and its modified materials, and nickel-cobalt-aluminum ternary material and its modified materials.

[0025] In the above implementation process, the modified materials of the nickel-cobalt-manganese ternary material and the nickel-cobalt-aluminum ternary material respectively refer to the materials obtained by doping or coating the nickel-cobalt-manganese ternary material or the nickel-cobalt-aluminum ternary material.

[0026] In some embodiments, the molar content ratio of Ni in the ternary of the ternary system material is 0.4 - 0.7.

[0027] In the above implementation process, the ternary system material with a Ni molar content of 0.4 - 0.7 has good conductivity, and can reduce the conductivity difference between the first positive electrode active material layer and the second positive electrode active material layer with less addition of conductive agent, thereby reducing the deterioration of gas generation under high-temperature and high-voltage conditions and reducing the decrease in the energy density of the entire positive electrode sheet. At the same time, controlling the Ni molar content to be 0.4 - 0.7 can reduce the loss of the ternary system material during cycling. In addition, it can also reduce the possibility of performance deterioration when applied at high voltages such as 2.5 - 4.4 V.

[0028] In some embodiments, the ternary system material includes Li a Ni b Co c M1 d M2 e O f R g , where 0.75 ≤ a ≤ 1.2, 0.4 < b < 0.7, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is selected from one or two elements of Mn or Al, M2 is selected from one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R is selected from one or more elements of N, F, S, Cl.

[0029] In some embodiments, the thickness of the second positive electrode active material layer does not exceed 62% of the thickness of the entire positive electrode active material layer.

[0030] In the above implementation process, since the specific surface area of ​​the polyanion positive electrode material is large and it is easy to absorb water, when used as a battery, it is easy to cause a high hydrofluoric acid content in the battery to deteriorate the electrical performance. Therefore, controlling the thickness of the second positive electrode active material layer to not exceed 62% of the thickness of the entire positive electrode active material layer can reduce its deterioration of the battery's electrical performance.

[0031] In some embodiments, the positive electrode active material layer further includes an intermediate layer, the intermediate layer is disposed between the first positive electrode active material layer and the second positive electrode active material layer, and the intermediate layer includes a hydrophobic conductive polymer.

[0032] In the above implementation process, by providing a hydrophobic intermediate layer between the first positive electrode active material layer and the second positive electrode active material layer, the damage to the ternary system material caused by water absorption by the polyanion positive electrode material can be reduced.

[0033] In some embodiments, the hydrophobic conductive polymer includes at least one of polypyrrole, polyaniline, polythiophene, and polyacetylene.

[0034] In some embodiments, the intermediate layer further includes a hydrophobic conductive carbon material.

[0035] In the above implementation process, by adding hydrophobic conductive carbon substances, the intermediate layer has better conductivity, thereby reducing its influence on the electrical properties of the positive electrode active material layer.

[0036] In some embodiments, the hydrophobic conductive carbon-based material includes hydrophobic carbon nanotubes and / or hydrophobic carbon nanofibers.

[0037] In the second aspect, the present application provides a positive electrode sheet, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the thickness of the second positive electrode active material layer does not exceed 62% of the thickness of the entire positive electrode active material layer; the first positive electrode active material layer includes a first positive electrode active material and a first conductive agent, the second positive electrode active material layer includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, and the second positive electrode active material includes LiMPO 4 , M includes Mn and non-Mn elements, the non-Mn elements include one or both of a first doping element and a second doping element, the first doping element is manganese doping, the second doping element is phosphorus doping, the first positive electrode active material includes a ternary system material, the molar content of Ni in the ternary system material is 0.4-0.7, the powder resistivity F of the second positive electrode active material in Ω·cm at 8Mpa and the weight proportion C of the first conductive agent in the first positive electrode active material layer satisfy the following relationship:

[0038] In the technical solution of the embodiment of the present application, by controlling the addition amount C of the first conductive agent matched with the ternary system material with poor electronic conductivity and the LiMPO with good electronic conductivity 4 The powder resistivity F at 8Mpa satisfies To reduce the difference in conductivity between the first positive electrode active material layer and the second positive electrode active material layer, thereby improving the electrical performance of the entire positive electrode sheet. 4 Layered setting can reduce the ternary system materials and LiMPO 4 The possibility of current unevenness between the two makes the positive electrode have a higher capacity retention rate in the early stage of the cycle. 4 Usually show better safety performance, ternary system materials usually show higher energy density, using LiMPO 4 Using the ternary system material as the second positive electrode active material and the ternary system material as the first positive electrode active material enables the positive electrode sheet to have both higher safety performance and higher energy density.

[0039] In a third aspect, the present application provides a battery cell, the battery cell comprising the positive electrode sheet provided in the first aspect or the second aspect.

[0040] In a fourth aspect, the present application provides a battery, the battery comprising the battery cell provided in the third aspect.

[0041] In a fifth aspect, the present application provides an electrical device, which includes the battery cell provided in the third aspect or the battery provided in the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0043] Figure 1 A schematic diagram of the structure of a vehicle provided in some embodiments of the present application;

[0044] Figure 2 A schematic diagram of the exploded structure of a secondary battery provided in some embodiments of the present application;

[0045] Figure 3 A schematic diagram of the structure of a battery cell provided in some embodiments of the present application;

[0046] Figure 4 An exploded view of a battery cell provided for some embodiments of the present application;

[0047] Figure 5 A first structural schematic diagram of a positive electrode sheet provided in some embodiments of the present application;

[0048] Figure 6 A second structural schematic diagram of a positive electrode sheet provided in some embodiments of the present application;

[0049] Figure 7 A flow chart of a method for preparing a positive electrode sheet provided in some embodiments of the present application.

[0050] The reference numerals in the specific implementation manner are as follows:

[0051] 1000-vehicle; 100-secondary battery; 200-motor; 300-controller; 10-housing; 11-accommodating space; 12-first part; 13-second part; 20-battery cell; 21-housing; 211-opening; 22-end cover assembly; 221-end cover; 222-electrode terminal; 23-electrode assembly; 231-positive electrode sheet; 2311-positive current collector; 2312-positive active material layer; 2312a-first positive active material layer; 2312b-second positive active material layer; 24-current collecting member; 25-insulating protection member. DETAILED DESCRIPTION

[0052] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0054] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0055] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0056] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0057] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0058] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0059] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0060] At present, from the perspective of market development, the application of power batteries is becoming more and more extensive. Power batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding.

[0061] The power battery can be a lithium-ion battery, which is widely used in portable electronic devices, electric vehicles and other fields. In the production process of lithium-ion secondary battery electrode plates, a single-layer coating is usually used to coat the required active material on the current collector. With the increase in energy density and safety performance requirements, some people have proposed the use of positive electrode active materials with high energy density characteristics such as ternary system materials and positive electrode active materials with high safety performance characteristics such as polyanion positive electrode materials to take into account energy density and safety performance.

[0062] However, when a positive electrode active material with high energy density characteristics and a positive electrode active material with high safety performance characteristics are simultaneously incorporated into a positive electrode active material layer 2312, current unevenness is likely to occur between the two positive electrode active materials in the positive electrode active material layer 2312. This phenomenon will cause the positive electrode sheet 231 to decay rapidly in the early stage of the cycle, which will have a great impact on the cycle retention rate of the positive electrode sheet 231.

[0063] In order to further improve the problem of rapid attenuation of the electrode in the early stage of the cycle, the two active materials can be layered. However, after the layered arrangement, the conductivity difference between the two layers of positive electrode active material is large, so that the positive electrode 231 still has the problem of poor electrical performance.

[0064] Based on the above considerations, in order to reduce the conductivity difference between each positive electrode active material layer and improve the electrical performance. The present application proposes a positive electrode sheet, the positive electrode sheet 231 includes a positive electrode active material layer 2312, the positive electrode active material layer 2312 includes a first positive electrode active material layer 2312a and a second positive electrode active material layer 2312b, the first positive electrode active material layer 2312a includes a first positive electrode active material and a first conductive agent, the second positive electrode active material layer 2312b includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, the powder resistivity F of the second positive electrode active material in Ω·cm at 8Mpa and the weight proportion C of the first conductive agent in the first positive electrode active material layer 2312a satisfy the following relationship:

[0065] In such a positive electrode sheet 231, by controlling the addition amount C of the first conductive agent matched with the first positive electrode active material with poor electronic conductivity and the powder resistivity F of the second positive electrode active material with good electronic conductivity at 8Mpa to meet To reduce the difference in conductivity between the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b, thereby improving the electrical performance of the entire positive electrode sheet 231. At the same time, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby allowing the positive electrode sheet 231 to have a higher capacity retention rate in the early stage of the cycle.

[0066] The positive electrode sheet 231 can be used to prepare an electrode assembly 23, and the electrode assembly 23 can be used in, but not limited to, an electric device such as a vehicle 1000, a ship or an aircraft. A power supply system of the electric device can be composed of a battery cell 20 and a secondary battery 100 disclosed in the present application, so that it is conducive to giving full play to the effect of the positive electrode material with a high ultimate compaction density on the compaction density of the entire positive electrode active material layer 2312, achieving a good improvement in the compaction density of the entire positive electrode active material layer 2312, thereby improving the energy density of the positive electrode sheet 231 and improving the capacity of the battery cell 20.

[0067] The embodiment of the present application provides an electric device using a battery as a power source, and the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0068] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device according to an embodiment of the present application.

[0069] Please refer to Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A secondary battery 100 is provided inside the vehicle 1000, and the secondary battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The secondary battery 100 may be used to power the vehicle 1000, for example, the secondary battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 300 and a motor 200, and the controller 300 is used to control the secondary battery 100 to power the motor 200, for example, for starting, navigating and driving the vehicle 1000.

[0070] In some embodiments of the present application, the secondary battery 100 can be used not only as an operating power source for the vehicle 1000 , but also as a driving power source for the vehicle 1000 , replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000 .

[0071] In the present application, the secondary battery 100 may refer to a single battery cell 20, or it may refer to a single physical module including multiple battery cells 20 to provide higher voltage and capacity, which may be in the form of a battery pack, a battery module, etc. The secondary battery 100 may include a case 10 for encapsulating multiple battery cells 20, and the case 10 may prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.

[0072] Figure 2 This is a schematic diagram of the exploded structure of a secondary battery 100 provided in some embodiments of the present application. Figure 2 The secondary battery 100 includes a housing 10 and a battery cell 20 , and the battery cell 20 is accommodated in the housing 10 .

[0073] The box body 10 is used to provide a storage space 11 for the battery cell 20. In some embodiments, the box body 10 may include a first portion 12 and a second portion 13, and the first portion 12 and the second portion 13 cover each other to define the storage space 11 for accommodating the battery cell 20. Of course, the connection between the first portion 12 and the second portion 13 can be sealed by a sealing member (not shown in the figure), and the sealing member can be a sealing ring, a sealant, etc.

[0074] The first part 12 and the second part 13 can be in various shapes, such as a cuboid, a cylinder, etc. The first part 12 can be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20, and the second part 13 can also be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20. The opening side of the second part 13 covers the opening side of the first part 12, thereby forming a box body 10 with a receiving space 11. Of course, if Figure 2 As shown, the first part 12 may be a hollow structure with one side open, and the second part 13 may be a plate-like structure. The second part 13 covers the open side of the first part 12 to form a box body 10 with an accommodating space 11.

[0075] In the secondary battery 100, there are multiple battery cells 20, and the multiple battery cells 20 can be connected in series, in parallel, or in mixed connection. Mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 can be directly connected in series, in parallel, or in mixed connection, and then the whole body formed by the multiple battery cells 20 is accommodated in the box 10; of course, multiple battery cells 20 can also be connected in series, in parallel, or in mixed connection to form a battery module, and then the multiple battery modules are connected in series, in parallel, or in mixed connection to form a whole body, and accommodated in the box 10. The battery cell 20 can be cylindrical, flat, rectangular, or other shapes. Figure 2 The example shows that the battery cell 20 is in a square shape.

[0076] In some embodiments, the secondary battery 100 may further include a busbar component (not shown), and the multiple battery cells 20 may be electrically connected via the busbar component to achieve series connection, parallel connection, or mixed connection of the multiple battery cells 20 .

[0077] Figure 3 This is a schematic diagram of the structure of a battery cell 20 provided in some embodiments of the present application. Figure 4 This is an exploded view of a battery cell 20 provided in some embodiments of the present application. Figure 3 and Figure 4 The battery cell 20 may include a housing 21 , an end cap assembly 22 and an electrode assembly 23 . The housing 21 has an opening 211 , the electrode assembly 23 is accommodated in the housing 21 , and the end cap assembly 22 is used to cover the opening 211 .

[0078] The shape of the housing 21 can be determined according to the specific shape of the electrode assembly 23. For example, if the electrode assembly 23 is a rectangular parallelepiped structure, the housing 21 can be a rectangular parallelepiped structure. Figure 3 and Figure 4 The case where the housing 21 and the electrode assembly 23 are square is exemplarily shown.

[0079] The shell 21 may also be made of a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc., and the embodiment of the present application does not impose any special restrictions on this.

[0080] The end cap assembly 22 includes an end cap 221 and an electrode terminal 222. The end cap assembly 22 is used to seal the opening 211 of the housing 21 to form a closed installation space (not shown), and the installation space is used to accommodate the electrode assembly 23. The installation space is also used to accommodate an electrolyte, such as an electrolyte. The end cap assembly 22 is a component for outputting the electrical energy of the electrode assembly 23. The electrode terminal 222 in the end cap assembly 22 is used to be electrically connected to the electrode assembly 23, that is, the electrode terminal 222 is electrically connected to the tab of the electrode assembly 23. For example, the electrode terminal 222 is connected to the tab through the current collecting member 24 to achieve electrical connection between the electrode terminal 222 and the tab.

[0081] It should be noted that the opening 211 of the shell 21 can be one or two. If the opening 211 of the shell 21 is one, the end cap assembly 22 can also be one, and two electrode terminals 222 can be provided in the end cap assembly 22, and the two electrode terminals 222 are respectively used to electrically connect to the positive pole ear and the negative pole ear of the electrode assembly 23. If the opening 211 of the shell 21 is two, for example, the two openings 211 are provided on opposite sides of the shell 21, and the end cap assembly 22 can also be two, and the two end cap assemblies 22 are respectively covered at the two openings 211 of the shell 21. In this case, the electrode terminal 222 in one end cap assembly 22 can be a positive electrode terminal, which is used to electrically connect to the positive pole ear of the electrode assembly 23; the electrode terminal 222 in the other end cap assembly 22 can be a negative electrode terminal, which is used to electrically connect to the negative electrode sheet of the electrode assembly 23.

[0082] In some embodiments, Figure 4 As shown, the battery cell 20 may further include an insulating protective member 25 fixed to the periphery of the electrode assembly 23, and the insulating protective member 25 is used to insulate and isolate the electrode assembly 23 from the housing 21. Exemplarily, the insulating protective member 25 is a tape bonded to the periphery of the electrode assembly 23. In some embodiments, there are multiple electrode assemblies 23, and the insulating protective member 25 is arranged around the periphery of the multiple electrode assemblies 23, and the multiple electrode assemblies 23 are formed into an integral structure to keep the electrode assembly 23 structurally stable.

[0083] The electrode assembly 23 includes a positive electrode sheet 231, a negative electrode sheet and a separator. The positive electrode sheet 231 includes a positive electrode collector 2311 and a positive electrode active material layer 2312. The positive electrode active material layer 2312 is coated on the surface of the positive electrode collector 2311. The positive electrode collector 2311 not coated with the positive electrode active material layer 2312 protrudes from the positive electrode collector 2311 coated with the positive electrode active material layer 2312. The positive electrode collector 2311 not coated with the positive electrode active material layer 2312 serves as a positive electrode tab.

[0084] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is coated on the surface of the negative electrode current collector, the negative electrode current collector not coated with the negative electrode active material layer protrudes from the negative electrode current collector coated with the negative electrode active material layer, and the negative electrode current collector not coated with the negative electrode active material layer serves as a negative electrode tab. The material of the negative electrode current collector may be copper, and the negative electrode active material may be carbon or silicon, etc. In order to ensure that a large current passes without melting, the number of positive electrode tabs is multiple and stacked together, and the number of negative electrode tabs is multiple and stacked together. The material of the isolation film may be PP (polypropylene) or PE (polyethylene), etc. In addition, the electrode assembly 23 may be a wound electrode assembly or a laminated electrode assembly, and the embodiments of the present application are not limited thereto.

[0085] Figure 5 This is a first structural schematic diagram of the positive electrode sheet 231 provided in some embodiments of the present application. Figure 6 A second structural schematic diagram of the positive electrode sheet 231 provided in some embodiments of the present application; see Figure 5 and Figure 6 , the embodiment of the present application provides a positive electrode sheet, the positive electrode sheet 231 includes a positive electrode active material layer 2312, the positive electrode active material layer 2312 includes a first positive electrode active material layer 2312a and a second positive electrode active material layer 2312b, the first positive electrode active material layer 2312a includes a first positive electrode active material and a first conductive agent, the second positive electrode active material layer 2312b includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, the powder resistivity F of the second positive electrode active material in Ω·cm at 8Mpa and the weight proportion C of the first conductive agent in the first positive electrode active material layer 2312a satisfy the following relationship:

[0086] The positive electrode active material layer 2312 is attached to at least part of the surface of the positive electrode collector 2311. The first positive electrode active material layer 2312a and the second active material layer in the positive electrode active material layer 2312 can both be in direct contact with the positive electrode collector 2311. In other words, the positional relationship between the first positive electrode active material layer 2312a, the second active material layer and the positive electrode collector 2311 can be: the first positive electrode active material layer 2312a is attached to the positive electrode collector 2311, and the second positive electrode active material layer 2312b is attached to the surface of the first positive electrode active material layer 2312a facing away from the positive electrode collector 2311; it can also be: the second positive electrode active material layer 2312b is attached to the positive electrode collector 2311, and the first positive electrode active material layer 2312a is attached to the surface of the second positive electrode active material layer 2312b facing away from the positive electrode collector 2311.

[0087] The material of the positive electrode current collector 2311 may be one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. Figure 5 In one embodiment, a first positive electrode active material layer 2312a and a second positive electrode active material layer 2312b are sequentially disposed on one surface of the positive electrode current collector 2311; please continue to refer to Figure 6 In another embodiment, the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b are sequentially disposed on both surfaces of the positive electrode current collector 2311. It should be noted that this is only an example of how this solution can be implemented. In other embodiments, the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b can be exchanged.

[0088] For lithium-ion batteries, the first positive electrode active material and the second positive electrode active material refer to substances that can intercalate and deintercalate lithium ions.

[0089] The conductive agent is to ensure that the electrode has good charge and discharge performance. A certain amount of conductive material is usually added during the production of the electrode sheet. It plays the role of collecting microcurrents between the active materials and between the active materials and the current collector to reduce the contact resistance of the electrode and accelerate the movement rate of electrons, thereby improving the charge and discharge efficiency of the electrode. The conductive agent can be at least one of conductive carbon black, carbon fiber, carbon nanotubes, Ketjen black, graphene or acetylene black. The first conductive agent refers to the conductive agent added to the first positive electrode active material layer 2312a. A conductive agent is often also added to the second positive electrode active material layer 2312b. For ease of description, the conductive agent is referred to as the second conductive agent in this application. The proportion of the second conductive agent in the second positive electrode active material layer 2312b is usually no more than 0.5%.

[0090] Powder resistivity, also known as powder resistivity, is the ratio between actual resistance value and theoretical resistance value. It is an indicator used to indicate the ability of powder materials to conduct current.

[0091] By controlling the addition amount C of the first conductive agent coordinated with the first positive electrode active material with poor electronic conductivity and the powder resistivity F of the second positive electrode active material with good electronic conductivity at 8Mpa, To reduce the difference in conductivity between the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b, thereby improving the electrical performance of the entire positive electrode sheet 231. At the same time, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby allowing the positive electrode sheet 231 to have a higher capacity retention rate in the early stage of the cycle.

[0092] Exemplarily, the powder resistivity F of the second positive electrode active material in Ω·cm at 8 MPa and the weight proportion C of the first conductive agent in the first positive electrode active material layer 2312a satisfy the relationship: The value of can be 3.6, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42 or 42.1, etc., and it can also be any value in the range of 3.5 to 42.1.

[0093] In the technical solutions of some embodiments of the present application, the powder resistivity F of the second positive electrode active material in Ω·cm at 8 MPa and the weight proportion C of the first conductive agent in the first positive electrode active material layer 2312a satisfy the following relationship: By controlling the addition amount C of the first conductive agent coordinated with the first positive electrode active material with poor electronic conductivity and the powder resistivity F of the second positive electrode active material with good electronic conductivity at 8Mpa, The difference in conductivity between the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b can be further reduced, and the electrical performance of the entire positive electrode sheet 231 can be further improved. At the same time, the addition of the first conductive agent can be further reduced, and the deterioration of the first conductive agent on gas generation under high temperature and high voltage conditions can be reduced.

[0094] In the technical solutions of some embodiments of the present application, the powder resistivity of the second positive electrode active material at 8Mpa is 10-80Ω·cm; the weight proportion of the first conductive agent in the first positive electrode active material layer 2312a is 1.9%-2.8%; the powder resistivity of the first conductive agent at 8Mpa is ≤0.025Ω·cm. By controlling the powder resistivity of the second positive electrode active material, the content of the first conductive agent in the first positive electrode material active layer is kept within a more appropriate range, and the proportion of the first positive electrode active material is maintained within a higher range, thereby reducing the decrease in the energy density of the entire positive electrode sheet 231. At the same time, the powder resistivity of the second positive electrode active material at 8Mpa is within the range of 10-80Ω·cm, which can also take into account its own cycle performance.

[0095] Exemplarily, the powder resistivity of the second positive electrode active material at 8 MPa can be 10Ω·cm, 15Ω·cm, 20Ω·cm, 25Ω·cm, 30Ω·cm, 35Ω·cm, 40Ω·cm, 45Ω·cm, 50Ω·cm, 55Ω·cm, 60Ω·cm, 65Ω·cm, 70Ω·cm, 75Ω·cm and 80Ω·cm, etc., and it can also be any value in the range of 10 to 80Ω·cm. The weight proportion of the first conductive agent in the first positive electrode active material layer 2312a can be 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7% and 2.8%, etc., and it can also be any value in the range of 1.9% to 2.8%; the powder resistivity of the first conductive agent at 8Mpa can be 0.005Ω·cm, 0.010Ω·cm, 0.015Ω·cm, 0.020Ω·cm or 0.025Ω·cm, etc., and it can also be any value in the range of ≤0.025Ω·cm.

[0096] In the technical solutions of some embodiments of the present application, the first positive electrode active material includes a ternary system material; the second positive electrode active material includes a polyanion positive electrode material.

[0097] Polyanion positive electrode materials are a general term for a series of compounds containing tetrahedral or octahedral anion structural units (XOm)n-. They have the advantages of high charge and discharge voltage, large energy storage capacity, fast charge and discharge capability and good cycle stability. Their synthesis methods mainly include: high temperature solid phase method, sol-gel method, hydrothermal method, electrospinning method, etc.

[0098] Ternary system materials usually include two types: NCA and NCM. Among them, NCA is widely used because of its long life, large capacity, high energy density and other characteristics, but its specific heat capacity is relatively low; NCM combines the advantages of three types of positive electrode materials: lithium cobalt oxide, lithium nickel oxide and lithium manganese oxide, and has obvious ternary synergistic effect. NCM can usually be expressed as: LiNi x Co y Mn z O 2 .

[0099] Polyanion positive electrode materials usually exhibit good safety performance, and ternary system materials usually exhibit higher energy density. Using polyanion positive electrode materials as the second positive electrode active material and ternary system materials as the first positive electrode active material can make the positive electrode sheet 231 have both higher safety performance and higher energy density.

[0100] In the technical solutions of some embodiments of the present application, the second positive electrode active material includes a polyanion positive electrode material. Optionally, the polyanion positive electrode material includes LiMPO 4 , M includes Mn and non-Mn elements.

[0101] It should be noted that the above-mentioned LiMPO 4 It is not a specific molecular structure formula, but a general expression of lithium manganese phosphate.

[0102] In the technical solutions of some embodiments of the present application, the non-Mn element includes one or both of a first doping element and a second doping element, the first doping element is manganese-doped, and the second doping element is phosphorus-doped.

[0103] In the technical solutions of some embodiments of the present application, the first doping element includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge.

[0104] In the technical solutions of some embodiments of the present application, the first doping element includes at least two of Fe, Ti, V, Ni, Co and Mg.

[0105] In the technical solutions of some embodiments of the present application, the second doping element includes one or more elements selected from the group consisting of B, S, Si and N.

[0106] In the technical solutions of some embodiments of the present application, the second positive electrode active material includes Li 1+x Mn 1-y A y P 1-z R z O 4 , Li 1+x Mn 1-y A y P 1-z R z O 4 wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.

[0107] In the technical solutions of some embodiments of the present application, the compound Li 1+x Mn 1-y AHr 1-z R 4 The preparation method may include the following steps:

[0108] (1) dissolving a manganese source, a source of an element A to be doped at the manganese position, and an acid in a solvent and stirring to generate a suspension of a manganese salt doped with the element A, filtering the suspension and drying the filter cake to obtain a manganese salt doped with the element A;

[0109] (2) adding a lithium source, a phosphorus source, an element R source, a solvent, and the manganese salt doped with element A obtained in step (1) into a reaction container, grinding and mixing to obtain a slurry;

[0110] (3) transferring the slurry obtained in step (2) to a spray drying device for spray drying and granulation to obtain granules;

[0111] (4) Sintering the particles obtained in step (3) to obtain a positive electrode active material.

[0112] In any embodiment, the manganese source may be a manganese-containing substance known in the art that can be used to prepare lithium manganese phosphate. For example, the manganese source may be selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, manganese carbonate, or a combination thereof.

[0113] The acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, organic acid such as oxalic acid, etc., for example, oxalic acid. The source of element R is selected from at least one of sulfate, borate, nitrate and silicate of element R. The source of element A is selected from at least one of simple substance, oxide, phosphate, oxalate, carbonate and sulfate of A.

[0114] In the technical solutions of some embodiments of the present application, the polyanion positive electrode material includes Li h A i Mn 1-j B j P 1-k C k O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.

[0115] It should be noted that Li h A i Mn 1-j B j P 1-k C k O 4-l D l The compound is actually a specific LiMPO 4 Materials. The preparation method can refer to Li 1+x Mn 1-y A y P 1-z R z O 4 , no limitation is made here.

[0116] Below is Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 The preparation process is further described as follows: 1. Preparation of doped manganese oxalate: 1.3 mol of MnSO 4 ﹒ H 2 O, 0.7 mol FeSO 4 ﹒ H 2O was fully mixed in a mixer for 6 hours. The mixture was transferred to a reactor, and 10L of deionized water and 2mol of dihydrated oxalic acid (in terms of oxalic acid) were added. The reactor was heated to 80°C and stirred at 600rpm for 6 hours. The reaction was terminated (no bubbles were generated) to obtain an Fe-doped manganese oxalate suspension. The suspension was then filtered, and the filter cake was dried at 120°C and then ground to obtain a median particle size Dv 50 2. Preparation of doped lithium manganese phosphate: 1 mol of the above manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO 4 ) 3 , an aqueous solution of 85% phosphoric acid containing 0.999 mol of phosphoric acid, 0.001 mol of H 4 SiO 4 , 0.0005 mol NH 4 HF 2 and 0.005 mol sucrose were added to 20 L of deionized water. The mixture was transferred to a sand mill and fully ground and stirred for 10 hours to obtain a slurry. The slurry was transferred to a spray drying device for spray drying and granulation. The drying temperature was set to 250°C and dried for 4 hours to obtain particles. In a nitrogen (90% volume) + hydrogen (10% volume) protective atmosphere, the above powder was sintered at 700°C for 10 hours to obtain carbon-coated Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 .

[0117] In the technical solutions of some embodiments of the present application, the second positive electrode active material further has a carbon-containing coating layer.

[0118] The introduction of the carbon-containing coating layer improves the conductivity of the second positive electrode active material. At this time, the structure of the second positive electrode active material is actually LiMPO 4 The core has a core-shell structure in which the surface of the core is covered with a coating layer.

[0119] In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before adding the materials. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0120] In addition, due to the different preparation processes and conditions of the materials, the molar content of the O element is usually not strictly the coefficient of the O element in the chemical formula, and there will be fluctuations, such as Li 1+x Mn 1-y Ay P 1-z R z O 4 The molar content of the oxygen element is not strictly 4.

[0121] For example, the second positive electrode active material may be LiFePO 4 、LiMn 0.1 Fe 0.9 PO 4 、LiMn 0.2 Fe 0.8 PO 4 、LiMn 0.3 Fe 0.7 PO 4 、LiMn 0.4 Fe 0.6 PO 4 、LiMn 0.5 Fe 0.5 PO 4 、LiMn 0.6 Fe 0.4 PO 4 、LiMn 0.7 Fe 0.3 PO 4 、LiMn 0.8 Fe 0.2 PO 4 、LiMn 0.9 Fe 0.1 PO 4 、LiMnPO 4 、LiMn 0.5 Al 0.5 P 0.5 B 0.5 O 4 、LiMn 0.5 Mg 0.5 P 0.5 S 0.5 O 4 etc., LiMPO 4 The M in the formula includes Mn and non-Mn elements, the non-Mn elements include one or both of the first doping element and the second doping element, the first doping element is manganese doping, and the second doping element is phosphorus doping. The first doping element includes one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; the second doping element includes one or more elements of B, S, Si and N.

[0122] In the technical solutions of some embodiments of the present application, the powder resistivity of the second positive electrode active material at 8Mpa is 20 to 50Ω·cm. Polyanion positive electrode materials such as LiMPO4 The powder resistivity is often negatively correlated with the surface carbon coating amount. The lower the powder resistivity, the higher the carbon coating amount. The surface carbon coating will also deteriorate the storage gas production under high temperature and high voltage conditions. Therefore, by controlling the powder resistivity of the second positive electrode active material at 8Mpa to 20-50Ω·cm, the possibility of significant deterioration in gas production can be reduced while taking into account its own cycle performance.

[0123] In the technical solutions of some embodiments of the present application, the ternary system materials include nickel-cobalt-manganese ternary materials and modified materials thereof and nickel-cobalt-aluminum ternary materials and modified materials thereof. The modified materials of nickel-cobalt-manganese ternary materials and the modified materials of nickel-cobalt-aluminum ternary materials refer to materials obtained by doping or coating nickel-cobalt-manganese ternary materials or nickel-cobalt-aluminum ternary materials, respectively. The coated coating layer can be selected as a combination of one or more oxides, nitrates, phosphates, and carbonates containing one or more elements of Al, Ba, Zn, Ti, Co, W, Y, Si, Sn, B, and P, such as Al2O3, B2O3, TiO2, etc. For example, the chemical formula of the ternary system material is LiNi x Co y Mn z O 2 , where 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1.

[0124] In the technical solutions of some embodiments of the present application, the molar content of Ni in the ternary system material accounts for 0.4 to 0.7. The ternary of the ternary system material refers to Ni, Co and Mn or Ni, Co and Al. The molar content of Ni in the ternary system material accounts for 0.4 to 0.7, which means the molar content of Ni accounts for the proportion of the total molar content of the ternary. For example, in NCM, the molar content ratio is calculated as Ni molar content / (Ni molar content + Co molar content + Mn molar content). If the ternary system material is doped at the Ni position, Co position or Mn position, the molar content of the doping element is added to the denominator for calculation. The ternary system material with a molar content of Ni of 0.4 to 0.7 has good conductivity, and can reduce the difference in conductivity between the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b with the addition of less conductive agent, thereby reducing the deterioration of gas production under high temperature and high voltage conditions and reducing the decrease in energy density of the entire positive electrode sheet 231. At the same time, controlling the molar content of Ni to 0.4-0.7 can reduce the loss of the ternary system material during the cycle. In addition, it can also reduce the possibility of performance deterioration when high voltage, such as 2.5-4.4V, is used.

[0125] Exemplarily, the molar content ratio of Ni in the ternary of the ternary system material can be 0.4, 0.5, 0.6, 0.7, etc., or it can also be any value within the range of 0.4 to 0.7.

[0126] In the technical solutions of some embodiments of the present application, the ternary system material includes LiaNibCocM1dM2eOfRg, where 0.75 ≤ a ≤ 1.2, 0.4 < b < 0.7, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is selected from one or two elements of Mn or Al, M2 is selected from one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R is selected from one or more elements of N, F, S, Cl.

[0127] Exemplarily, the first positive electrode active material can be a ternary positive electrode material, specifically it can be LiNi 0.4 Co 0.2 Mn 0.4 O 2 、LiNi 0.5 Co 0.2 Mn 0.3 O 2 和LiNi 0.7 Co 0.15 Mn 0.15 O 2 etc. In LiaNibCocM1dM2eOfRg, a can be any one or more values within the range of 0.75 to 1.2, b can be any one or more values within the range of 0.4 to 0.7, c can be any one or more values within the range of 0 to 1, d can be any one or more values within the range of 0 to 1, e can be any one or more values within the range of 0 to 0.2, f can be any value within the range of 1 to 2.5, and g can be any one or more values within the range of 0 to 1.

[0128] It should be noted that the above enumeration of the first positive electrode active material and the second positive electrode active material is only for illustrative purposes to show that the present solution can be implemented, and is not used to limit the present solution. The implementation of the present solution only requires that the first positive electrode active material and the second positive electrode active material meet the corresponding electronic conductivity requirements. In other embodiments, those skilled in the art can select the specific substances of the first positive electrode active material and the second positive electrode active material according to actual needs, such as the above-listed materials and their modified substances, and the modification includes doping or coating, etc., or select other materials that meet the electronic conductivity requirements of the present application. For example, the first positive electrode active material can be selected from lithium-rich manganese-based materials, lithium manganate materials, or lithium nickel manganate materials, etc.

[0129] In the technical solutions of some embodiments of the present application, the thickness of the second positive electrode active material layer 2312b does not exceed 62% of the thickness of the entire positive electrode active material layer 2312. Since the polyanion positive electrode material has a large specific surface area and is prone to water absorption, when used as a battery, it is easy to cause a high hydrofluoric acid content in the battery to deteriorate the electrical performance. Therefore, the thickness of the second positive electrode active material layer 2312b is controlled to be no more than 62% of the thickness of the entire positive electrode active material layer 2312, which can reduce the deterioration of the battery electrical performance.

[0130] Exemplarily, the thickness of the second positive electrode active material layer 2312b can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or 62% of the thickness of the entire positive electrode active material layer 2312, and it can also be any value in the range of 0 to 62% (excluding 0% and including 62%).

[0131] In the technical solutions of some embodiments of the present application, the positive electrode active material layer 2312 also includes an intermediate layer, which is arranged between the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b, and the intermediate layer includes a hydrophobic conductive polymer. By arranging a hydrophobic intermediate layer between the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b, the damage to the ternary system material caused by water absorption of the polyanion positive electrode material can be reduced.

[0132] The hydrophobic conductive polymer may be a polymer body that has hydrophobicity and conductivity, or a compound of a hydrophobic polymer and a conductive material. In the technical solutions of some embodiments of the present application, the hydrophobic conductive polymer includes at least one of polypyrrole, polyaniline, polythiophene and polyacetylene. In the technical solutions of other embodiments, the intermediate layer also includes hydrophobic conductive carbon substances. The hydrophobic conductive carbon substances include hydrophobic carbon nanotubes and / or hydrophobic carbon nanofibers. By adding hydrophobic conductive carbon substances, the intermediate layer has better conductivity, thereby reducing its influence on the electrical properties of the positive active material layer 2312.

[0133] After the above introduction to the material and structure of the positive electrode sheet 231 , the preparation method of the positive electrode sheet 231 will be specifically introduced below.

[0134] The preparation method of the positive electrode sheet 231 includes the following steps: sequentially preparing a positive electrode active material layer 2312 on a positive electrode current collector 2311, wherein the preparation order of the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b in the positive electrode active material layer 2312 is not limited, and may be: the first positive electrode active material layer 2312a is arranged on at least a portion of the surface of the positive electrode current collector 2311, and the second positive electrode active material layer 2312b is arranged on at least a portion of the surface of the first positive electrode active material away from the positive electrode current collector 2311; or: the second positive electrode active material layer 2312b is arranged on the positive electrode current collector 231 1, the first positive electrode active material layer 2312a is arranged on at least a portion of the surface of the second positive electrode active material layer 2312b away from the positive electrode current collector 2311; the first positive electrode active material layer 2312a includes a first positive electrode active material and a first conductive agent, the second positive electrode active material layer 2312b includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, and the powder resistivity F of the second positive electrode active material in Ω·cm at 8Mpa and the weight proportion C of the first conductive agent in the first positive electrode active material layer 2312a satisfy the following relationship:

[0135] The method controls the addition amount C of the first conductive agent matched with the first positive electrode active material with poor electronic conductivity and the powder resistivity F of the second positive electrode active material with good electronic conductivity at 8Mpa to meet To reduce the difference in conductivity between the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b, thereby improving the electrical performance of the entire positive electrode sheet 231. At the same time, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby allowing the positive electrode sheet 231 to have a higher capacity retention rate in the early stage of the cycle.

[0136] Figure 7 For a flow chart of a method for preparing the positive electrode sheet 231 provided in some embodiments of the present application, please refer to Figure 7 The present application embodiment provides a method for preparing a positive electrode sheet 231, the method comprising:

[0137] S110, preparing a first positive electrode active slurry: dispersing a first positive electrode active material, a binder and a conductive agent in a solvent to form a first positive electrode active slurry. The first positive electrode active material may be the first positive electrode active material described above, for example, a material having a chemical formula of LiNi x Co y Mn z O 2, (0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1) ternary system material, optionally, a small amount of other positive electrode active materials may be added.

[0138] For the specific selection of the ternary system material, reference may be made to the selection of the ternary system material in the first positive electrode active material layer 2312 a in the aforementioned positive electrode sheet 231 , which will not be described in detail here.

[0139] The binder may be one or more of styrene-butadiene rubber, water-based acrylic resin, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, polyvinyl alcohol and polyvinyl butyral. The conductive agent may be at least one of conductive carbon black, carbon fiber, carbon nanotube, Ketjen black, graphene or acetylene black. The solvent may be one or more of dimethyl glutarate and N-methyl pyrrolidone. A leveling agent, a dispersant, etc. may also be added to the first positive electrode active slurry.

[0140] S120, preparing a second positive electrode active slurry: dispersing a second positive electrode active material, a binder and a conductive agent in a solvent to form a second positive electrode active slurry. The second positive electrode active material may be the second positive electrode active material described above, for example, a material having a chemical formula of LiMn a Fe 1-a PO 4 , (0≤a≤1) polyanion positive electrode material, and optionally a small amount of other positive electrode active materials may be added.

[0141] For the specific selection of the polyanion positive electrode material, reference may be made to the selection of the polyanion positive electrode material in the second positive electrode active material layer 2312 b in the aforementioned positive electrode sheet 231 , which will not be described in detail here.

[0142] The binder, the conductive agent and the solvent may be the binder, the conductive agent and the solvent in the first positive electrode active slurry, etc. The binder in the first positive electrode active slurry may be the same as or different from the binder in the second positive electrode active material; the conductive agent in the first positive electrode active slurry may be the same as or different from the conductive agent in the second positive electrode active material; the solvent in the first positive electrode active slurry may be the same as or different from the solvent in the second positive electrode active material. At the same time, a leveling agent, a dispersant, etc. may also be added to the second positive electrode active slurry, which is not limited in this application.

[0143] S130, preparing the first positive electrode active material layer 2312a: coating the first positive electrode active slurry on the surface of the positive electrode current collector 2311, and then drying to form the first positive electrode active material layer 2312a. The coating can be applied to one surface or both surfaces of the positive electrode current collector 2311 according to requirements.

[0144] The coating method may be: scraping, roller coating, slit coating, etc., which is not limited in this application. It should be noted that step S120 and step S130 can be interchanged or performed simultaneously, which is not limited in this application.

[0145] S140, preparing the second positive electrode active material layer 2312b: coating the second positive electrode active slurry on the surface of the first positive electrode active material layer 2312a, and then drying to form the second positive electrode active material layer 2312b. During coating, the second positive electrode active material layer 2312b can be formed on the surface of the first positive electrode active material layer 2312a according to the situation of the first positive electrode active material layer 2312a.

[0146] S150 , rolling the second positive electrode active material layer 2312 b to obtain the positive electrode sheet 231 .

[0147] It should be noted that the above is only an example of sequentially arranging the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b on the positive electrode current collector 2311. In other embodiments, the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b can be exchanged.

[0148] After the positive electrode sheet 231 is prepared, the first isolation film, the positive electrode sheet 231, the second isolation film and the negative electrode sheet are stacked in sequence, wound to form a wound flat structure, and then hot pressed to obtain a wound electrode assembly; or, after the positive electrode sheet 231 is prepared, the positive electrode sheet 231, the isolation film, the negative electrode sheet, the isolation film, and so on, are stacked in sequence to form a stacked electrode assembly.

[0149] The electrode assembly 23 can be used to prepare a battery cell 20 , and the battery cell 20 can be used to prepare a secondary battery 100 and provide electric energy to an electric device.

[0150] Next, one or more embodiments are described in more detail with reference to the following examples. Of course, these examples do not limit the scope of one or more embodiments.

[0151] Examples and Comparative Examples

[0152]

Preparation of positive electrode

[0153] Preparation of the first positive electrode active material layer: the first positive electrode active material NCM, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone (NMP), wherein the mass proportion of the binder polyvinylidene fluoride (PVDF) is 2.5%, and the mixture is stirred to obtain a first coating layer slurry; then the slurry is mixed at 30mg / 1540.25mm 2 The mass of the positive electrode active material is evenly coated on the positive electrode current collector and dried to obtain a first positive electrode active material layer.

[0154] Preparation of the second positive electrode active material layer: The second positive electrode active material LiMn 0.6 Fe 0.4 PO 4 , conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 96.5:1:2.5, and stirred and mixed to obtain a second coating layer slurry; then the slurry was added at 70mg / 1540.25mm 2 The mass is evenly coated on the second positive electrode active material layer, and after drying, it is rolled and die-cut to obtain a lithium-ion battery positive electrode sheet.

[0155]

Preparation of negative electrode sheet

[0156] The active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC) are dissolved in the solvent deionized water in a mass ratio of 90:5:3:2, and mixed evenly to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil once or multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.

[0157]

Preparation of electrolyte

[0158] In an argon atmosphere glove box (H 2 O<0.1ppm, O 2 <0.1ppm), mix the organic solvents ethylene carbonate (EC) / diethyl carbonate (DEC) / ethyl methyl carbonate (EMC) in a volume ratio of 1 / 1 / 1, add 1 mol / L LiPF 6 The lithium salt is dispersed uniformly, and then 5% fluoroethylene carbonate is dissolved in the above organic solvent and stirred uniformly to obtain an electrolyte.

[0159]

Isolation film

[0160] A polyethylene film is used as the isolation film.

[0161]

Preparation of lithium-ion batteries

[0162] The prepared positive electrode sheet, negative electrode sheet and separator (polyethylene (PE) porous polymer film) are made into corresponding battery cells according to the Z-shaped stacking structure. The battery cells are vacuum dried at 90°C for 12 hours, and then the positive and negative pole tabs are ultrasonically welded. The positive pole tabs are aluminum tabs, and the negative pole tabs are nickel tabs. The positive and negative pole tabs are located on the same side of the battery cell. The battery cells after the tabs are welded are placed in aluminum-plastic films of appropriate sizes for top-side sealing. The top-side sealing temperature is 145°C, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes the processes of static, hot and cold pressing, formation, shaping, and capacity testing in sequence to obtain a lithium-ion battery product.

[0163] The main parameters of each embodiment and comparative example are shown in the following table:

[0164]

[0165] In the above table, the chemical formula of NCM with a Ni content of 0.55 is LiNi 0.55 Co 0.05 M 0.4 O 4 The chemical formula of NCM with a Ni content of 0.65 is LiNi 0.65 Co 0.07 M 0.28 O 4 The chemical formula of NCM with Ni content of 0.4 is LiNi 0.4 Co 0.05 M 0.55 O 4 The chemical formula of NCM with a Ni content of 0.7 is LiNi 0.7 Co 0.07 M 0.23 O 4 The chemical formula of NCM with a Ni content of 0.33 is LiNi 0.33 Co 0.05 M 0.62 O 4 The chemical formula of NCM with Ni content of 0.83 is LiNi 0.83 Co 0.12 M 0.05 O 4 .

[0166] The test of carbon content C in the first positive electrode active material layer includes: taking the first positive electrode active material layer powder of the electrode sheet, the weight of which must be ≥100 mg, placing it in a ceramic crucible and heating it to 1000°C for 4 hours (this step can remove the influence of the binder in the first positive electrode active material layer on the carbon content and prepare the test sample at the same time), and after the crucible and the residue therein are cooled to room temperature 25°C, they are placed in the HCS-140 high frequency infrared carbon-sulfur analyzer for carbon content analysis.

[0167] The positive electrode material powder resistivity test includes: the test equipment is Yuanneng Technology PRCD2100 powder resistivity tester, first weigh 0.2g of sample and add it to the sample cavity of the equipment mold, put the mold into the pre-compactor, turn on the pre-compactor to vibrate the powder, and then open the equipment software to start the test and get the test results.

[0168] The Ni content test of NCM material includes: taking 0.4g of the electrode NCM material layer powder in a 25ml beaker, adding 2ml~5ml nitric acid, leaving it overnight, and then placing it on an electric hot plate, heating it at about 100°C (using a voltage-regulating transformer to adjust the input voltage and temperature control), adding 0.5ml perchloric acid after the powder is digested, heating and digesting it at about 140°C until the white smoke is gone, and the residue should be white, otherwise nitric acid and perchloric acid should be added again to repeat the digestion, and finally using 7% (volume % of acid, the same below) hydrochloric acid to dissolve and extract, and after the volume is fixed to an appropriate volume depending on the content of the element to be tested, the mass fraction of Ni, Co, Mn, and Li is tested on the ICP-OES test instrument. The mass of different elements can be calculated based on the mass of the powder and the mass fraction of different elements, and then the molar amount can be calculated based on its molar mass. The Ni content can be confirmed by the molar ratio of different elements.

[0169] Embodiment 14

[0170] This embodiment is the same as Embodiment 3 except that the order of the first positive electrode material active layer and the second positive electrode active material layer is exchanged.

[0171] The performance test was performed on the batteries provided in each embodiment and comparative example, and the performance test specifically included:

[0172] 25℃ cycle test: The lithium-ion battery product prepared above is charged to 4.4V at 0.5C at 2.5~4.4V in a constant temperature environment of 25℃, then charged at a constant voltage at 4.4V to a current ≤0.05C, left to stand for 5min, and then discharged to 2.5V at 1C. The capacity is recorded as Cn (n=1,2,3……). The above operation is repeated. The capacity retention rate is calculated according to the ratio of Cn / C3. When Cn / C3×100%=80%, the corresponding number of cycles is extracted as the examination index of the cycle capacity.

[0173] 25℃ cyclic internal resistance growth test: ① Initial internal resistance test: The prepared soft-pack laminated battery is charged to 4.4V at 0.5C at 2.5-4.4V in a constant temperature environment of 25℃, and then charged at a constant voltage of 4.4V to a current ≤0.05C. After standing for 30 minutes, the voltage U1 is recorded, and then the battery is discharged at 1C for 30 seconds, and the voltage at 30 seconds is recorded as U2. The internal resistance 1 = (U1-U2) / 1C; ② Post-cycle internal resistance test: After the battery with the initial internal resistance tested is tested for cycle performance according to the cycle test, the internal resistance 2 is tested again. The internal resistance growth rate = (internal resistance 2-internal resistance 1) / internal resistance 1.

[0174] High-temperature storage gas production test: The length, width and height of the soft-pack laminated battery prepared above were tested in a constant temperature environment of 25°C to calculate the battery volume V1 = length × width × height. The battery was then placed in a constant temperature box at 60°C ± 2°C for 50 days. On the 50th day, the battery was taken out and the length, width and height of the battery were immediately tested to obtain the volume V2 after high-temperature storage. The volume change rate was (V2-V1) / V1.

[0175] The test results are shown in the following table:

[0176]

[0177]

[0178] It can be seen from the above table that when the positive electrode sheet provided in the embodiment of the present application is used as a battery, the battery has better cycle performance and smaller internal resistance growth.

[0179] By comparing the data of Examples 1 to 5 and Comparative Examples 1 to 2, it can be seen that as the F / (C*100) ratio gradually increases, the number of cycles shows a trend of first increasing and then decreasing, and the cycle internal resistance growth rate shows a trend of first decreasing and then increasing, and when the F / (C*100) ratio is between 3.6 and 42.1, the number of cycles is more than 1000, and the cycle internal resistance growth rate is within 32%. It can be seen that the F / (C*100) ratio is between 3.6 and 42.1. It is a better range. In particular, when the F / (C*100) ratio is in the range of 8 to 23.5, the number of cycles is more than 1200.

[0180] By comparing the data of Example 3 and Examples 6 to 10, it can be obtained that as the Ni content in NCM increases, the number of cycles shows a trend of first increasing and then decreasing, and the cycle internal resistance growth rate shows a trend of first decreasing and then increasing. When the Ni content in NCM is between 0.4 and 0.7, the number of cycles is more than 980, and the cycle internal resistance growth rate is within 41%. It can be seen that the Ni content in NCM is in the range of 0.4 to 0.7, which is a better range.

[0181] By comparing the data of Example 3 and Examples 11 to 12, it can be obtained that when the thickness of the second positive electrode active material layer accounts for less than 62%, the number of cycles is more than 1000 cycles, and the cycle internal resistance growth rate is within 42%. When the thickness accounts for 70%, the cycle performance and internal resistance growth deteriorate significantly. It can be seen that the thickness of the second positive electrode active material layer is less than 62%, which is a better range.

[0182] By comparing the data of Example 3 and Example 13, it can be seen that the number of cycles can be further increased by providing an intermediate layer between the first positive electrode active material layer and the second positive electrode active material layer. The inventors analyzed that the reason may be that the hydrophobic intermediate layer can reduce the damage of the polyanion positive electrode material to the ternary system material by water absorption, thereby achieving good cycle performance and a smaller cycle internal resistance increase.

[0183] By comparing the data of Example 3 and Example 14, it can be seen that placing the ternary system material closer to the current collector is more conducive to maintaining the cycle performance and controlling the cycle internal resistance. The inventors analyzed that the reason may be that placing the ternary system material in the inner layer can reduce the occurrence of side reactions with the electrolyte, thereby achieving good cycle performance and a smaller cycle internal resistance increase.

[0184] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer includes a first positive electrode active material and a first conductive agent, the second positive electrode active material layer includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, and the powder resistivity F of the second positive electrode active material in Ω·cm at 8 MPa and the weight proportion C of the first conductive agent in the first positive electrode active material layer satisfy the following relationship:

2. The positive electrode sheet according to claim 1, characterized in that: The powder resistivity F of the second positive electrode active material in Ω·cm at 8 MPa and the weight proportion C of the first conductive agent in the first positive electrode active material layer satisfy the following relationship:

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The powder resistivity of the second positive electrode active material at 8 MPa is 10 to 80 Ω·cm; and / or The weight percentage of the first conductive agent in the first positive electrode active material layer is 1.9% to 2.8%; and / or The powder resistivity of the first conductive agent at 8 Mpa is ≤0.025 Ω·cm.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The first positive electrode active material comprises a ternary system material; and / or The second positive electrode active material includes a polyanion positive electrode material.

5. The positive electrode sheet according to claim 4, characterized in that: The ternary system materials include nickel-cobalt-manganese ternary materials and modified materials thereof and nickel-cobalt-aluminum ternary materials and modified materials thereof; and / or The polyanion positive electrode material includes LiMPO4, M includes Mn and non-Mn elements, the non-Mn elements include one or both of a first doping element and a second doping element, the first doping element is manganese doping, and the second doping element is phosphorus doping.

6. The positive electrode sheet according to claim 5, characterized in that: The first doping element includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; and / or The second doping element includes one or more elements selected from the group consisting of B, S, Si and N.

7. The positive electrode sheet according to claim 5, characterized in that: The polyanion positive electrode material includes Li 1+x Mn 1- y A y P 1-z R z O4, wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.

8. The positive electrode sheet according to claim 5, characterized in that: The polyanion positive electrode material includes Li h A i Mn 1- j B j P 1-k C k O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.

9. The positive electrode sheet according to any one of claims 4 to 8, characterized in that: The polyanion positive electrode material also has a coating layer containing carbon.

10. The positive electrode sheet according to claim 9, characterized in that: The powder resistivity of the second positive electrode active material at 8 MPa is 20 to 50 Ω·cm.

11. The positive electrode sheet according to claim 5, characterized in that: The molar content of Ni in the ternary material of the ternary system is 0.4-0.

7.

12. The positive electrode sheet according to claim 5, characterized in that: The ternary system material includes Li a Ni b Co c M1 d M2 e O f R g , where 0.75 ≤ a ≤ 1.2, 0.4 < b < 0.7, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is selected from one or two elements of Mn or Al, M2 is selected from one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R is selected from one or more elements of N, F, S, Cl.

13. The positive electrode sheet according to claim 4, characterized in that: The thickness of the second positive electrode active material layer does not exceed 62% of the thickness of the entire positive electrode active material layer.

14. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The positive electrode active material layer further includes an intermediate layer disposed between the first positive electrode active material layer and the second positive electrode active material layer, wherein the intermediate layer includes a hydrophobic conductive polymer.

15. The positive electrode sheet according to claim 14, characterized in that: The hydrophobic conductive polymer includes at least one of polypyrrole, polyaniline, polythiophene and polyacetylene.

16. The positive electrode sheet according to claim 14 or 15, characterized in that: The intermediate layer also includes a hydrophobic conductive carbon material.

17. The positive electrode sheet according to claim 16, characterized in that: The hydrophobic conductive carbon material includes hydrophobic carbon nanotubes and / or hydrophobic carbon nanofibers.

18. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the thickness of the second positive electrode active material layer does not exceed 62% of the thickness of the entire positive electrode active material layer; the first positive electrode active material layer includes a first positive electrode active material and a first conductive agent, the second positive electrode active material layer includes a second positive electrode active material, the electronic conductivity of the second positive electrode active material is greater than the electronic conductivity of the first positive electrode active material, the second positive electrode active material includes LiMPO4, M includes Mn and non-Mn elements, the non-Mn element includes one or two of a first doping element and a second doping element, the first doping element is manganese doping, and the second doping element is phosphorus doping, the first positive electrode active material includes a ternary system material, the molar content of Ni in the ternary of the ternary system material accounts for 0.4 to 0.7, and the powder resistivity F of the second positive electrode active material in Ω·cm at 8Mpa and the weight proportion C of the first conductive agent in the first positive electrode active material layer satisfy the following relationship:

19. A battery cell, characterized in that: The battery cell comprises the positive electrode sheet according to any one of claims 1 to 18.

20. A battery, characterized in that: The battery comprises the battery cell of claim 19.

21. An electrical device, characterized in that: The electrical device comprises the battery cell according to claim 19 or the battery according to claim 20.

Citation Information

Patent Citations

  • Positive electrode for secondary battery and lithium secondary battery comprising same

    CN108475772A

  • Lithium ion secondary battery and preparation method thereof

    CN112216822A

  • Positive plate and preparation method thereof, electrode assembly, battery monomer, battery and electric equipment

    CN115939305A

  • Positive electrode active material, positive electrode plate, electrode assembly, battery monomer, battery and electric equipment

    CN115939322A

  • Positive pole piece, secondary battery and electric equipment

    CN116314602A